The The Effect of Rational and Irrational Sentiments of Individual and Institutional Investors on Indonesia Stock Market - Elly Zunara; Achsani, Noer Azam; Hakim, Dedi Budiman; Sembel, Roy (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The study's goal is to explore the relationship between investor sentiment, stock return, and volatility in Indonesian markets, with a focus on the Indonesia Stock Exchange (IDX). This research looked at the Indonesia Stock Exchange's (IDX) monthly statistics on stock trading volume from January 2015 to January 2021 to infer the attitudes of both institutional and retail investors. The analysis also uses a variety of well-known and accepted factors from the literature on asset pricing, such as the Covid-19 index, a reliable indicator of Indonesia's underlying market conditions. Error Correction Model was used to analyze a regression between investor sentiment and fundamentals in the Indonesian stock market in order to determine the impact of macroeconomic and Covid-19 risk variables on sentiment (ECM). Next, it looked at how unexpected shifts in Indonesian investor sentiment affected stock returns and IDX volatility with the help of Impulse response functions (IRFs) derived from a Vector Error Correction Model (VECM) model. Individual and institutional investors' stock market returns and IDX volatility were found to be affected more by rational than by irrational attitudes, according to the empirical findings. Keywords: investor sentiment, IDX, stock returns, volatility, VECM